Meta Analisis Pengaruh Bahan Ajar Fisika Terhadap Hasil Belajar Siswa - Miftahurrahmi Miftahurrahmi; Shinta Sari Oktavia; Desnita Desnita (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
This study aims to determine the effect of physics teaching materials on student learning outcomes. The type of research used is a meta-analysis that analyzes 25 pre-existing national articles starting from 2013-2019. The data analysis technique used is to calculate the effect size for each article. Based on the results of the study, it was found that physics teaching materials had an effect on student learning outcomes. So that it is known that first, the influence of physics teaching materials on student learning outcomes from 25 articles obtained an average effect size of 1.1308 with a very high category. The effect of the two teaching materials based on education level with the highest effect size is at the junior high school level, namely 1,395 with a very high category. The third is based on the highest effect size class level in class VIII, namely 1,395 with a very high category. Fourth, based on the type of teaching materials with the highest effect size, namely 1,418 with a very high category on teaching materials. The fifth effect magnitude based on the highest learning material is found in the material for parabolic motion, circular motion and Newton's law, which is 3.29 with a high effect category. Sixth, based on the unit method, strategy, and model, the highest effect size is 2.19 with the category having a high impact on the student recap strategy.